Analisis Tentang Hadits-Hadits Tujuan Pendidikan Dalam Islam - Alinna Alinna; Juliana Juliana; Khairunnisya Khairunnisya; Tia Salsabilla; Wismanto Wismanto (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The purpose of education in Islam is the most important element in Islamic education. This is indicated by the significant number of verses in the Qur'an and the Prophet's Hadith relating to education or science. There are many studies related to the goals of education in Islam, but have not comprehensively demonstrated the desired educational goals. This study aims to describe the educational objectives of the Prophet's hadith perspective in the book of Shahihain. By using a library approach, the author concludes that the goals of education in the book of Shahihain are devotion to Allah, making students have noble character, goodness in life in the world and the hereafter and forming a strong believer personality.